Reliability and Validity of the Chinese (Mandarin) Tinnitus Handicap Inventory - Zhaoli Meng; Yun Zheng; Shixi Liu; Kai Wang; Xiudan Kong; Yong Tao; Ke Xu; Guanjian Liu (Clinical and Experimental Otorhinolaryngology, 2012)
ObjectivesThe Tinnitus Handicap Inventory (THI) is a commonly used self-reporting tinnitus questionnaire. We undertook this study to determine the reliability and validity of the Chinese-Mandarin version of the Tinnitus Handicap Inventory (THI-CM) for measuring tinnitus-related handicaps.MethodsWe tested the test-retest reliability, internal reliability, and construct validity of the THI-CM. Two-hundred patients seeking treatment for primary or secondary tinnitus in Southwest China were asked to complete THI-CM prior to clinical evaluation. Patients were evaluated by a clinician using standard methods, and 40 patients were asked to complete THI-CM a second time 14±3 days after the initial interview.ResultsThe test-retest reliability of THI-CM was high (Pearson correlation, 0.98), as was the internal reliability (Cronbach's α, 0.93). Factor analysis indicated that THI-CM has a unifactorial structure.ConclusionThe THI-CM version is reliable. The total score in THI-CM can be used to measure tinnitus-related handicaps in Mandarin-speaking populations.